Evaluación del efecto de cuatro sustratos para pilones en amaranto (amaranthus caudatus l) variedad selenaya sosulka, Salache, Latacunga-Cotopaxi, 2023. - Zumba Unapanta, Adrian Ismael (2024)
In the present investigation it was proposed to find a suitable substrate in the pylons, to reduce the loss in the germination of the species, the test was located at the Technical University of Cotopaxi, Faculty of Agricultural Sciences and Natural Resources, greenhouse of Andean grains; with the objective of evaluating the effect of four substrates for pylons in amaranth (Amaranthus caudatus L) variety selenaya sosulka. The methodological approach applied in this study was experimental with the following substrates: KEKKILA peat substrate, Baltic Tray Substrate, BM4, BM2, with a completely randomized block experimental design (DBCA), with fourteen treatments and three replications, obtaining 42 experimental units. The results of the study in relation to the variables, T11 (Peat substrate KEKKILA 50% + Baltic Tray Substrate 25% + BM4 25%), in germination percentage obtained a mean of 86.13%, seedling height with a mean of 1.37 cm, stem diameter with a mean of 1.07 mm, number of leaves occupies the A range and a mean of 4.97 true leaves, root length with a mean of 10.65 cm, root volume with a mean of 0.05 cm and root volume with a mean of 0.05 cm; root volume with a mean of 0.13 ml, pH with a mean of 7.37 which was the highest in the A range.